Hydro-morphodynamic responses of detached breakwater in mangrove rehabilitation project / Arniza Fitri - Arniza, Fitri (2018)
The coastal hydro-morphodynamic to detached breakwater are site specific that vary widely among different cases. This study attempts to investigate the coastal hydro-morphodynamic changes due to the presence of an existing design of detached breakwater at a representative cohesive intertidal area of Carey Island, Malaysia. In addition, the seabed level in the mangrove degradation area due to changes of the various configurations of geometry and position of the detached breakwater in the study site were also investigated. Regarding the morphodynamic changes in the mangrove degradation area, bed profiling activities in the vicinity of the breakwater were done after three to six years of construction of the breakwater. Bed profiling data in the vicinity of breakwater before and one year after breakwater‟s installation were obtained from a previous study. For evaluating the changes of coastal hydrodynamic characteristics including nearshore currents, nearshore waves and sediment transport patterns, a coastal hydraulic study using MIKE 21 2D numerical model was carried out at the site. To verify the accuracy of simulation results, the values of root-mean square error (RMSE), coefficient of determination (R2) and Theil‟s coefficients were calculated. Further, the calibrated MIKE 21 model was used to simulate the bed level changes in the degraded mangrove area after changing the design parameters of existing detached breakwater. Based on the values of RMSE (e.g. 0.07 – 0.09 m/s), R2 (e.g. 0.82 to 0.94) and Theil‟s coefficients (e.g. 0.06 – 0.18), it is evident that the models were well calibrated and validated against field conditions. The simulation results show that the presence of detached breakwater at intertidal area of Carey Island has reduced the current speeds and significant wave heights approximately up to 0.14 m/s and 0.9 m, respectively in protected area behind its structure. The reduction of current speeds and significant wave heights behind the structure created more calm hydrodynamic conditions in the mangrove degradation area and increased the settling velocities of sediments due to flock formation. Thus, it helped in settling down suspended sediments. In addition, field monitoring showed that the presence of detached breakwater has trapped sediment accumulations in the vicinity of its structure and increased the seabed elevations in the mangrove degradation area. However, average increase of seabed elevations during six years period of breakwater installation with existing design is not significant for mangrove rehabilitation project. Based on results from numerical model, by increasing the height and length of the detached breakwater approximately by 1 m and 50 m, respectively, detached breakwater in the study site can increase the seabed elevations in the mangrove degradation area approximately by 0.73 m during six years of breakwater installation. It means that the presence of detached breakwater with higher and longer dimensions can optimize the increase of the bed level elevations in mangrove degradation area and thus, it would support the success of mangrove rehabilitation project in the site.